+0  
 
0
7
1
avatar+624 

Solve for the variable x in terms of y and z, assuming y \neq \frac{1}{2}:
xy + x = \frac{3x + 2y + z + y + 2z}{3}

 Feb 20, 2024

Best Answer 

 #1
avatar+394 
+2

\(xy + x = \frac{3x + 2y + z + y + 2z}{3}\)

\(xy+x=\frac{3x+3y+3z}{3}\).

\(xy+x=x+y+z\)

\(xy=y+z\)

\(x=\frac{y+z}{y}\). Can also be written as: \(x=1+\frac{z}{y}\).

 Feb 20, 2024
 #1
avatar+394 
+2
Best Answer

\(xy + x = \frac{3x + 2y + z + y + 2z}{3}\)

\(xy+x=\frac{3x+3y+3z}{3}\).

\(xy+x=x+y+z\)

\(xy=y+z\)

\(x=\frac{y+z}{y}\). Can also be written as: \(x=1+\frac{z}{y}\).

hairyberry Feb 20, 2024

3 Online Users

avatar
avatar